GENDERING MUSICAL DISCOURSE - Asare, Amos Darkwa (International Library of African Music, 2023)
In this article, I apply a gendered analysis to a healing phenomenon understood through indigenous musical performances in a ritual context. Ghanaian indigenous music has been widely researched and documented, however, a contextual analysis of the gendered musical roles associated with the healing rituals of the Twelve Apostles Church (TAC) is scant. In this research, the data was obtained from six congregations of the TAC, between 2014 to 2019. Based on participation, observations and interviews, the analysis is a description of how music is gendered in the indigenous healing rituals of the TAC. The main question I seek to answer is: how is gender constructed and how are the gender roles ascribed to musical performances in the healing rituals of the TAC? In answering this question, I discuss the cultural interpretations ascribed to gender in a musically informed healing ritual. The findings revealed that in the TAC, singing is mostly initiated by females who sing about illnesses. Males, on the other hand, are mostly in charge of playing the dondo, an hourglass drum. However, the mfoba, an enmeshed rattle is played by both males and females and it is the mfoba that aids spirit possession. Spirit possession is an integral part of the healing rituals of the TAC and females are more susceptible to being possessed by spirits than males. Based on various rules I argue that the healing ritual of the TAC is based on complementary rather than opposing musical roles of males and females.
Keywords: Healing; Musical instruments; Gender; Ritual; Mfoba (Instrument); Ghana; Gender Roles; Dondo (Instrument); Indigenous Music; African Music